(untitled) (Texas Journal of Medical Science, 2022)
Work related stress is recognized worldwide as a major challenge for the health of workers especially nurses. Nursing has been identified as one of the most stressful jobs. Work-related stress in nurses affects both individual and organizational functioning as well as health care. A descriptive study was conducted among the nurses of the critical care units in the medical city to assess the work-related stress and determine Socioeconomic Status for nurses at Critical Care Unit. A non- probability (purposive) sample of (200) nurses who were working at Critical Care was chosen. The questionnaire was developed by the researcher; It consists of three parts; the first one (nurse demographic data) consists of (7) items; the second part (Socioeconomic Status scale) consists of (13) items, and Perceive stress scale which consists of (10) items. The data was collected by using a questionnaire and analysed through Statistical Package for the Social Sciences (version24.0) using a descriptive statistical approach (frequency, percentage, mean of score, standard deviation) and inferential statistical approach (chi_sequre test). The result reveals that, all staff nurses who are working in Critical Care Unit suffer from stress; that nurses working in critical care units are experiencing severe stress (71%). Motivational and specification programs for workers in critical care units are exposed to work pressure, and encourage nurses for working in critical units by giving awards and increase of encouragement, Working providing a sufficient number of nurses in critical units to avoid nursing shortage in critical care unit, and increase level of income